Quantification of diazotrophs bacteria isolated from cocoa soils (Theobroma cacao L.), by the technique of Most Probable Number (MPN) - Adriana Zulay Argüello Navarro; Niccolay Madiedo Soler; Laura Yolima Moreno Rozo (Revista Colombiana de Biotecnología, 2016)
The objective of this research was to quantify diazotrophic bacteria and compare physicochemically rhizospheric soils of three cocoa plantations (Theobroma cacao L.) in Norte de Santander Department, Colombia; for which they were characterized, differing in cultivated area, agronomic management and crop age. From serial dilutions of the samples and using the technique of Most Probable Number (MPN), In semisolid culture media (NFb, JMV, LGI, JNFb), the diazotrophs were quantified, evaluating as positive the formation of a subsurface film in the medium contained in sealed vials; equal samples were sent to the Bioambiental laboratory (UNET) for physicochemical analyzes. As a result, the evaluated samples showed deficiencies in the percentage of organic matter and elements such as Potassium, Phosphorus and Magnesium. Statistically highly significant differences in MPN were reported. The highest quantification of diazotrophs was reported in the Florilandia farm, which was characterized by drip irrigation. The highest quantification of diazotrophs was recorded in the media NFb and JMV, demonstrating a greater presence of the presumed genera Azospirillum sp. and Burkholderia sp. which are easily isolated from rhizospheric soils, unlike the genera Herbaspirillum sp. and Gluconacetobacter sp. which by their endophytic character tend to be less predominant in this type of samples. It is also concluded that the physicochemical characteristics of the soil, humidity and climatic relationships at the moment of sampling, condition the amount of root exudates and therefore are factors that conditioned the presence of diazotrophs in the samples.